2020
DOI: 10.1111/acfi.12606
|View full text |Cite
|
Sign up to set email alerts
|

Trade credit and cost stickiness

Abstract: Using a large sample of US data, we examine the relation between trade credit and cost behaviour and further investigate the moderating effects on this relation of agency problem, product market competition, and customer concentration. We find that firms using high levels of trade credit exhibit lower cost stickiness and this is prevalent in the high agency problem sub‐sample. In addition, in a non‐competitive market, where the agency problem arises owing to lack of competition, trade credit plays an external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 124 publications
(185 reference statements)
0
12
0
Order By: Relevance
“…We find that the mean (median) AP/TA and AP/COGS are 0.068 (0.054) and 0.135 (0.110), respectively. These statistics are within the range of prior studies (Kling et al ., 2014; Zhang et al ., 2014; Hasan and Habib, 2019; Costa and Habib, 2021). The CIDH1 (i.e., the natural logarithm of CEO debt‐to‐equity ratio) and CIDH2 (i.e., the natural logarithm of the CEO‐to‐firm debt‐to‐equity ratio) have means of 0.158 and 0.122, respectively, which are largely consistent with prior studies (see, e.g., Wei and Yermack, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We find that the mean (median) AP/TA and AP/COGS are 0.068 (0.054) and 0.135 (0.110), respectively. These statistics are within the range of prior studies (Kling et al ., 2014; Zhang et al ., 2014; Hasan and Habib, 2019; Costa and Habib, 2021). The CIDH1 (i.e., the natural logarithm of CEO debt‐to‐equity ratio) and CIDH2 (i.e., the natural logarithm of the CEO‐to‐firm debt‐to‐equity ratio) have means of 0.158 and 0.122, respectively, which are largely consistent with prior studies (see, e.g., Wei and Yermack, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In the first measure, we follow Aktas et al (2012) and Ferrando and Mulier (2013) by calculating the ratio of accounts payable scaled by total sales (TC1). In the second measure (TC2), we follow Love et al (2007) , Molina and Preve (2012) , Afrifa et al (2018) , Li et al (2020) and Costa and Habib (2020) by cacluating the ratio of accounts payable (AP) scaled by cost of goods sold (COGS).…”
Section: Methodsmentioning
confidence: 99%
“…For example, trade credit alleviates asymmetric information between suppliers and customers by incorporating the lending relation of the private information. Trade credit also permits a reduction in precautionary money holdings and provides a cost‐effective and flexible way to moderate the potential problems of underinvestment and moral hazard (Ferris, 1981; Mian and Smith Jr, 1992; Biais and Gollier, 1997; Fabbri and Menichini, 2010; Giannetti et al ., 2011; Kieschnick et al ., 2013; Dass et al ., 2015; Costa and Habib, 2020). In addition, some studies have shown that the substitution of bank and trade credit is intervened by social trust (Lemmon and Roberts, 2010; Levine et al ., 2018), debt enforcement (Sautner and Vladimirov, 2018) and conflicts between trade creditors and bank creditors (Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%